(De)construction of women’s images in select literary pieces of (her)stories in Southeast Asia - Pandapatan, Alican Mendez (Passage: Journal of English Language and Literature, 2025)
Feminism draws attention to advancing women’s rights and socio-economic development, more specifically, to obtain equality. However, this movement to exalt women’s status is lacking in the experience of Southeast Asia (SEA) women. This study looks into the construction of women in selected short stories. The study design is qualitative within a critical discourse analysis (CDA) of Norman Fairclough. To dissect the data, a literary analysis of the literary elements of short stories is the first step which directs its focus on women. Second, the women’s image is constructed or deconstructed based on decolonial feminism. A decision method framework was created to construct the characters in the herstories and if there is a need to deconstruct due to misrepresentation. It is revealed that the experiences of these women narrate the condition they live in. It is also seen that image is constructed when the description and feminist perspectives (general feminism and Decolonial feminism) are similar, meanwhile, when it opposes, a deconstruction based on decolonial feminism is required. The study has limitations on the sample literary pieces studied and does not generally scope the overall SEA society, therefore, further studies on literary pieces or genres representing all the SEA nations can provide a deeper exploration of this topic.